Customer Retention and Loyalty toward Local Commercial Banks in Malaysia - Yong IngIng, Annie; Raimee, Nuraishahbinti; a/p G Narayana Nair, Malathi Nair; Teck Keong, Wong; a/l Chelliah, Mahendra Kumar; Ee Soon Cha; Sook Ching, Lim (International Journal of Psychosocial Rehabilitation, 2019)
Introduction: Nowadays, the organizations are concerned with their customers, especially in the industry of banking. Therefore, customer retention and loyalty are crucial within the operations of business. Previous studies investigated the different factors affecting the customer retention and loyalty. The objective of this study is to identify the antecedents of customer retention and loyalty among the bank users of local commercial banks in Malaysia. Design and methodology: Five different factors were included in this study to verify the relationship of customer retention and loyalty among local commercial banks users. SPSS was used to test the five hypotheses. 300 respondents were interviewed via questionnaire. Results and findings: SPSS software was adopted to analyse the data. It discovered that the switching costs and customer trust have significant relationship towards the customer retention and loyalty among the bank users in local commercial banks in Malaysia. Origin and Contribution: This study filled the gaps of the literature in the customer retention and loyalty of bank users among the local commercial banks. In the practical implication, this study contributed that there is the relationship between switching costs and customer trust among the bank users of local commercial banks in Malaysia.